Climate, conflict and security in global livestock systems - Synnestvedt, Thea; Maviza, Gracsious; Pacillo, Grazia (International Livestock Research Institute, 2024)
The livestock sector is critical in sustaining livelihoods. It contributes to food security and supports economies worldwide. Livestock systems are vital sources of livelihood and income, food and nutrition and cultural identity for millions of people. However, these systems are increasingly under threat from the intertwined challenges of climate change impacts, conflict and insecurity. As the climate crisis intensifies, its impacts are felt acutely in the agricultural sector, with livestock systems being particularly vulnerable due to their dependency on climate-sensitive resources such as water and pasture. Climate security is concerned about how climate change-related risks and vulnerabilities compound existing risks and vulnerabilities in communities and with what impacts peace and security. Notably, climate change has observable negative impacts on economies, populations and resource availability and access, which may lead to displacement, making it a risk multiplier of vulnerabilities and social tensions within communities. Livestock systems are deeply intertwined with climate security, as they are both contributors and victims of climate change. The relationship between climate security and livestock systems is complex and often cyclical. On one hand, climate change poses significant threats to the viability of livestock systems, while on the other hand, livestock systems contribute to climate change through greenhouse gas emissions and environmental degradation. This creates a feedback loop where livestock production exacerbates climate change, which then further stresses livestock systems, potentially leading to conflict and insecurity. Thus, climate change worsens ecological stressors, such as droughts, floods and desertification, which in turn fuel competition for scarce resources. This competition often leads to conflicts, especially in regions where governance is weak and traditional mechanisms for resource-sharing are eroding. These conflicts not only disrupt livestock production but also threaten broader societal stability, as they can lead to displacement, loss of livelihoods and heightened food insecurity.